The Effect of the P.M.I strategy on the achievement of fifth grade students in science (Journal of the College of Basic Education, 2023)
The research aims to identify the impact of the P.M.I strategy on the achievement of fifth grade students in science, and to verify the aim of the research, the following null hypothesis was formulated: There is no statistically significant difference at the level (0.05) between the mean scores of the students of the experimental group who will study according to the P.M.I strategy and the average scores of the control group who will study according to the usual method of achievement.The current research community represented the students of the fifth grade of primary school in the morning public schools for boys affiliated to the Directorate of Education of the Baghdad Governorate, Al-Rusafa, for the academic year (2022-2023), as it reached (74) primary schools for boys. (As the number of its students reached (85) students in three divisions (A - B - C), and by simple random assignment, the research sample was chosen to represent (50) students in two divisions (AB) with (24), (26) students, respectively, as Division (a) represented the experimental group that studied according to the steps of the P.M.I strategy, and division (b) the control group that studied according to the usual method .The experimental design with partial control was chosen for the two experimental and control groups with a post-test for the achievement of the fifth grade primary students .The experiment was applied in the classroom. The first academic session lasted (10) weeks, and the content of the first three units, including the first five chapters, was analyzed according to Bloom's classification of the cognitive field for levels (remembering, comprehension, application, analysis, and synthesis), as it reached 164 "behavioral" goals. Prepared (23) daily teaching plans for the experimental group using the M.I. strategy. The same applies to the control group according to the usual methodThe students of the research sample (experimental and control) were rewarded in some variables that may affectThe results of the research are (intelligence, previous information, and previous achievement).The researcher prepared the research tool, which is the achievement test, as it reached (28) multiple-choice objective paragraphs with four alternatives. In this regard, the researcher took an agreement rate of (85%) or more as a criterion for accepting each paragraph of the test, as the experts agreed on the validity and integrity of all test paragraphs. Thus, the apparent validity of the tool and the validity of the content were verified through the test map, as the validity of the content for the achievement test reached (75%) .) After completing the application of the experiment, the achievement test was conducted on the students of the research sample (the experimental group) and the control group, and the data were analyzed statistically, the results of the research, "depending on the statistical bag (spss), and the results showed the superiority of the students of the experimental group who studied using the .P.M strategy in the achievement test over their peers in the control groupStatistical and the size of a significant impact on the collectionIn the light of the research results, the researcher recommends using the P.M.I strategy in teaching as an alternative to the methodThe usual number of suggestions is suggested .